Analisis Kesulitan Guru Fisika dalam Menyusun dan Melaksanakan Penelitian Tindakan Kelas - Mawarni Saputri; Nurulwati; Susanna; Musdar (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Classroom Action Research (CAR) aims to improve the quality of the implementation of learning in the classroom. CAR has an important and strategic role in efforts to improve the quality of learning. Therefore, it is very important for teachers to carry out CAR and make scientific research reports on CAR. However, the reality on the ground is that there are still many physics teachers at SMA Aceh Tamiang who have difficulty compiling Classroom Action Research (CAR). The purpose of this study was to find out the difficulties faced by teachers in implementing and compiling Classroom Action Research (CAR) reports. The results obtained that teachers' perceptions of CAR increased after participating in CAR training. Aspects of knowledge and skills are classified as good and the teacher's attitude towards CAR is classified as very good. The results of the difficulty analysis showed that respondents (physics teachers) found it very difficult to report the results of CAR, and overall it can be concluded that respondents still find it difficult to implement and prepare CAR.